2018
DOI: 10.1051/matecconf/201819602025
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of groundwaters pressure distribution in the underground structures by cylindrical form zone

Abstract: A mathematical model is developed for studying the distribution of groundwater pressure and its variation in the zone of underground structures of a cylindrical shape. Based on the created model, the influence of the thickness of the aquifer, the soil porosity, the filtration coefficient, the viscosity coefficient and the piezoelectric conductivity coefficient on the pressure that groundwater exerts on the lower part of the underground structure is investigated. The analysis of the possibility of pushing the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 3 publications
(1 reference statement)
0
11
0
Order By: Relevance
“…In [5,6] it was shown that the use of transition floors, which allow isolating damage zones, is the most economical and reliable. It is this technique that has been applied in some buildings of Moscow City in the form of a system of 5-10-story frame blocks above the communication floor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [5,6] it was shown that the use of transition floors, which allow isolating damage zones, is the most economical and reliable. It is this technique that has been applied in some buildings of Moscow City in the form of a system of 5-10-story frame blocks above the communication floor.…”
Section: Resultsmentioning
confidence: 99%
“…A shock may occur, for example, during the construction of a multi-story building or a multistorey or high structure during an emergency break of the sling, with careless securing of the cargo, careless rotation of the crane arm, etc. [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…According to the experiment results, data were obtained on the carrying capacity of centrally compressed concrete columns reinforced with carbon fiber, both with a discrete arrangement of bands (strips) made of composite material along the height of structures, and with their continuous wrapping (analogue of reinforced concrete holder) [13][14]. Test results analysis shows that reinforcement of concrete columns working in compression by winding them with carbon canvases led to an increase in bearing capacity for compression by 54%, while strengthening them with lamella increased the bearing capacity of columns only by 8%, and only the partial winding addition to lamella with canvases led to an increase in the compressive capacity by 35%.…”
Section: Discussionmentioning
confidence: 99%
“…The damage effect to the support nodes of beams and columns on the power resistance. The effect of node damage (changes in boundary conditions) is illustrated on the main elements of building frames -beams and columns [17][18][19][20][21][22][23][24][25].…”
Section: Wherementioning
confidence: 99%